Anaerobic hydrogen and methane production from low-strength beverage wastewater. (31st May 2019) - Lay, Chyi-How; Vo, Tan-Phat; Lin, Po-Yen; Abdul, Peer Mohamed; Liu, Chun-Min; Lin, Chiu-Yue
Abstract: In this study, the low-strength effluent from an equalization tank of the wastewater treatment plant in a beverage factory was used for the production of hydrogen and methane. The COD concentration of this low-strength wastewater was 2.9 ± 2.0 g COD/L. In a two-phase anaerobic fermentation system, the hydrogen-producing bioreactor was operated at HRT 8 h, while the methane-producing reactor operated at HRT 24 h. The maximum MPR, methane yield (MY), methane content and COD removal were 72 ± 31 mL/L-d, 58 ± 12 mL/g COD, 92 ± 2% and 78%, respectively. Energy efficiency in this study was calculated as follows, the maximum heating value was 2.2 × 10 8 kcal/y. The annual carbon-emission reduction was 8.8 × 10 4 kg CO2 /y, 5.2 × 10 4 kg CO2 /y, 7.2 × 10 4 kg CO2 /y when energy-equivalent coal, natural gas or fuel was used, respectively. Highlights: Low-strength wastewater can be used as substrate for two-stage fermentation. Cell wash-out can be avoided via immobilization at low HRT. Mesophilic fermentation is better than thermophilic for large-scale application. Two-stage fermentation emitted lower carbon than energy-equivalent fossil fuels.